2013
DOI: 10.1177/1059712313501347
|View full text |Cite
|
Sign up to set email alerts
|

Reading motor intention through mental imagery

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…Because this situation led to a less “optimized” motor performance, one may speculate that this strategy would be employed as an external signal during social interaction to show the agent’s social intention to share the object (Sartori et al, 2009a). Previous studies have supported this interpretation by showing that humans are sensitive to external kinematic characteristics of a movement, and especially trajectory height (Manera et al, 2011; Sartori et al, 2011; Lewkowicz et al, 2013). The new findings reported here demonstrate that even preparatory actions reflect the agent’s social intention and thus, movement properties may be read by perceivers for whom understanding motor intention from early kinematics is important.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Because this situation led to a less “optimized” motor performance, one may speculate that this strategy would be employed as an external signal during social interaction to show the agent’s social intention to share the object (Sartori et al, 2009a). Previous studies have supported this interpretation by showing that humans are sensitive to external kinematic characteristics of a movement, and especially trajectory height (Manera et al, 2011; Sartori et al, 2011; Lewkowicz et al, 2013). The new findings reported here demonstrate that even preparatory actions reflect the agent’s social intention and thus, movement properties may be read by perceivers for whom understanding motor intention from early kinematics is important.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, during social interaction, Boucher et al (2012) showed that human agents placed in a cooperative context are sensitive to the predictive information provided by the direction of gaze of their partners, even when interacting with robots. Furthermore, motor intention influences movement kinematics in such a way that not only the goal of individual actions can be anticipated by a perceiver (Lewkowicz et al, 2013), but also coordinated actions involving several agents can be performed (Knoblich and Sebanz, 2008; Vesper et al, 2010). Thus, it seems important for artificial social intelligence to develop (1) our knowledge of the specific effects that motor intention has on movement kinematics during a true social interactive task and (2) to provide solid guidelines for the development of optimal control models that will be able to implement intention in action in those artificial agents that need to cooperate intuitively with biological organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was also tested on tool-use where the spatial receptive fields of the parietal neurons associated to the hand extended to entail the tool (Goldenberg & Iriki, 2007;Maravita & Iriki, 2004). In terms of social cognition, this transformation mechanism is considered to take a central place in the process of understanding others as a mean to transform someone else visuo-motor perception into our own thus simulating their actions (Fogassi et al, 2005;Lewkowicz, Delevoye-Turrell, Bailly, Andry, & Gaussier, 2013;Meltzoff, 2007;Rizzolatti et al, 2001), see Fig. 1.…”
Section: Introductionmentioning
confidence: 91%
“…But more importantly, these findings are in line with a current motor cognition hypothesis (Ansuini, Cavallo, Bertone, & Becchio, 2014;Becchio, Manera, Sartori, Cavallo, & Castiello, 2012) that suggests that during our everyday actions, our intentions in action may be revealed in early trajectory patterns of simple movements. During social interaction, external observers would thus infer motor and social intention through the simple observation of the kinematic patterns of body motion (Herbort, Koning, van Uem, & Meulenbroek, 2012;Lewkowicz, Delevoye-Turrell, Bailly, Andry, & Gaussier, 2013;Sartori, Becchio, & Castiello, 2011). But to further test this hypothesis, interactivity for whole body motion is necessary.…”
Section: General Principlesmentioning
confidence: 99%